四轮驱动车辆动力传动系统的扭振分析计算 - 李春明; 魏来生; 江磊 (Jixie chuandong)
The effect of resonance of engine & transmission system and the characteristics of engine’s excitation are studied. Then the software TVSIM （Torsional Vibration SIMulation） programmed by authors is used to analyze the mode frequencies and mode shapes for the engine & transmission system of a 4×4-wheeled vehicle. The results show that although some mode frequencies are located in the range of engine’s excitation frequency,the harmful effect can be minimized if the engine’s running speed is properly limited.